One-step purification and freeze stability of papain at acidic pH values - Marković, Srđan; Milošević, Jelica; Đurić, Milica; Lolić, Aleksandar; Polović, Natalija (Archives of Biological Sciences, 2021)
Papain is a protease of great commercial value. The aim of this work was to provide a scalable, inexpensive, and simple papain purification procedure from papaya leaves that would enable the utilization of this by-product. Papain was purified by an optimized combination of salt precipitation at acidic pH. Its freeze stability was determined by activity and secondary structure recovery. Purification of papain at acidic pH values suppressed autoproteolysis and provided a high yield. The obtained protein was stored at slightly alkaline pH to avoid cold denaturation. The purification procedure may be of major importance for industrial, large-scale papain purification from papaya leaves. Abstract: Papain is a proteolytic enzyme of great commercial value. It is a cysteine protease highly expressed in Carica papaya fruit latex, but also present in papaya leaves. Purification procedures mostly deal with the latex and include a combination of precipitation and/or chromatographic techniques. Due to its solubility, structure and activity characteristics, the pH and salt content play significant roles in handling papain extracts. Here we report a simple, rapid and easily scalable procedure for papain purification from papaya leaves, which contain different contaminants as compared to papaya latex. Sodium chloride precipitation of contaminants at pH 5 followed by ammonium sulphate precipitation resulted in the removal of other leaf proteins and protein fragments from papain solution and about a 3-fold purification. The procedure also benefits from the suppression of autoproteolysis and preservation of the native structure, as confirmed by FTIR analysis, and the high recovery of activity of over 80%.